Experimental Confirmation of C-Rate Dependent Minima Shifts in Arrhenius Plots of Li-Ion Battery Aging. Issue 3 (1st March 2022) - Bozorgchenani, Maral; Kucinskis, Gints; Wohlfahrt-Mehrens, Margret; Waldmann, Thomas
Abstract : Li-ion batteries show a minimum of their aging rate at a certain temperature. This minimum in the corresponding Arrhenius plot expresses the longest cycle life at a certain C-rate. By characterizing aging of laboratory-made pouch cells and commercial 21700 cells as a function of C-rate and ambient temperature, we confirm that this minimum indeed shifts with the charging C-rate. Increasing C-rates lead to higher optimal ambient temperatures with respect to the aging rate. The differences between both cell types are discussed regarding the specific energy and anode coating thickness of the tested cells.